Pengelolaan Supervisi Pembelajaran Berbasis Kurikulum 2013 Di SMK Pancasila 3 Baturetno Kabupaten Wonogiri - , RIYANTO, Prof. Dr. Bambang Sumardjoko (2017)
The purposes of this study are: (1) to describe supervision planning for learning based on Curriculum 2013 in SMK Pancasila 3 Baturetno Wonogiri Regency. (2) to describe supervision implementation for learning based on Curriculum 2013 in SMK Pancasila 3 Baturetno Wonogiri Regency. (3) to describe the evaluation and follow-up of supervision for learning based on Curriculum 2013 in SMK Pancasila 3 Baturetno Wonogiri Regency. This research belongs to qualitative research with phenomenological design which conducted in SMK Pancasila 3 Baturetno. The techniques of data collection are in-depth interview, observation, and documentation. In analyzing the data, the researcher uses a descriptive-qualitative analysis model. The results of this study are: (1) supervision activity for learning in SMK Pancasila 3 Baturetno conducted by good planning. The principal and the vice principal of curriculum make a concept of supervision schedule according to applicable schedule and List Sort Ranks (DUK). Then, this concept is informed and coordinated to all teachers so that they know about this supervision activity. There are three aspects which supervised by principal, namely teaching administration, learning implementation, and assessment administration. (2) supervision for learning is done by observation technique. Principal supervises the class based on the supervision schedule. The assessment is set out in a supervisory instrument and principal's notebook in the form of scores and descriptions. (3) feedback and follow up supervision for learning is conducted after the supervised teacher has no teaching duty. feedback and follow up discusses the results of supervision, especially dealing with the strengths and weaknesses of the supervised teacher in carrying out the teaching and learning duties. In summary, the result of this study shows that teachers in SMK Pancasila 3 Baturetno have good teaching administration, are competent in delivering lessons, and have good assessment administration. However, some teachers have not understood the implementation of Curriculum 2013 completely. Therefore, the principal tries to facilitate them to hold some activities such as MGMP, IHT, or even engage them in Curriculum 2013 training as the follow-up of supervision activity for learning beside intensive guidance with GROW ME method. Key words : management, supervision and curriculum 2013